Hubungan Pemanfaatan Telemedicine Dengan Peningkatan Kepuasan Pasien, Kepatuhan Pasien Berobat dan Loyalitas Pasien di Rumah Sakit - Febrini Damayanti; Ascobat Gani (Syntax Idea)
Telemedicine has been proven to help a lot in health services. Telemedicine can also be a solution to the problem of difficulties in accessing health, limited human resources and making health costs more efficient. Previous research stated that the use of telemedicine plays a very important role in increasing patient satisfaction, patient adherence in treatment and patient loyalty. Unfortunately research on telemedicine in Indonesia is still very limited. This study aims to correlate the use of telemedicine with patient satisfaction, patient adherence and patient loyalty. The research method is a systematic literature review using prisms and data obtained online via Google Scholar, and PubMed. The results of the study prove that the use of telemedicine can increase patient satisfaction, patient adherence and patient loyalty.